Implementasi Kebijakan Pengembangan Obyek Wisata Pantai Bone Pololoba Desa Lopito Di Dinas Pariwisata Kabupaten Banggai Kepulauan - Samkamaria, Samkamaria; Widana, Alifa Raema; Safari, Cepi Triana (Jurnal ADMINISTRATOR, 2024)
Banggai Islands Regency is one of the districts in Central Sulawesi which has very beautiful natural tourist destinations. Based on data from 2020-2023, the Banggai Islands Tourism Office has a total of 82 natural tourist destinations, and 12 artificial tourist destinations. One of the natural tourist destinations that is currently viral among the people of Banggai Islands Regency is the Bone Pololoba beach tourist attraction located in Lopito Village. Currently, Bone Pololoba beach tourism is one of the leading tourist destinations in Banggai Islands Regency, especially among instagramable people. Bone Pololoba beach tourism is geographically located in Lopito Village, Totikum District. The panorama and beauty of Bone Pololoba beach which is still very natural attracts the attention of both local and foreign tourists to come to visit the Bone Pololoba panatai tourism site. Based on the results of the research, the implementation of the development of Bone Pololoba beach tourism objects carried out by the Tourism Office has not been carried out effectively. To find out why the implementation of the Bone Pololoba Beach tourism development policy at the Banggai Islands Tourism Office has not been effective, the author uses the Donald Van Metter and Carl Van Horn theoretical approach, to look at aspects (standards, measures of goals and policies, resources, characteristics of implementing agents, attitudes / tendencies, communication between implementing organizations and implementing activities, and the economic, social and political environment). Data collection methods were conducted through observation, direct interviews and documentation. Informant selection technique using purposive technique. From the results of the implementation of the Bone Pololoba Beach tourism object policy, it has not been effective. This is because there are still shortcomings in several aspects. Among them are the resources referred to in this case are limited human resources, and both financial and other supporting infrastructure